An Assessment Regarding Business Ethics: A Challenging Concept in Accounting Profession - Demır, Ozcan; Tasar, Sezin Acik; Narlıkaya, Zülküf (My University, 2023)
In business life, every company has a necessity of applying business ethics in order to drive code of conduct for both the company itself and its employees. Business ethics emerges as a set of principles and procedures evaluating the actions taken in business life according to social, moral and belief dimensions. Accounting profession is affected by the concept of business ethics, depending on whether accountants act in accordance with business ethics while carrying out professional activities or not. The aim of this study is to determine the perception levels of professional accountants working in TRB1 cities towards accounting professional ethics in terms of different variables. In addition, as a sub-objective, the relationship between the ethical perception of the accounting profession and its sub-dimensions was examined. The study is important as it is the first study covering TRB1 provinces in the literature. In the first parts of the study, business ethics concept and literature review were realized. In the research part, a survey was conducted to 312 accountants in TRB1 Region (Malatya-Elazığ-Bingöl and Tunceli) to reveal their aspect to business ethics. According to the results of the study, female accountants, the accountants between the ages of 41 and 55 and the accountants with master degree had higher accounting business ethics perception with respect to the ones in other groups. In contrast, it was observed that professional experience did not show a significant difference on the perception of business ethics of the participant groups. A relationship was also obtained in between the accounting business ethics perception and its sub-dimensions.
Keywords: Code of Ethics; Accounting Profession; Business Ethics; TRB1 Region; Unethical Behaviour; Business Ethics Perception